2020
DOI: 10.1155/2020/8820582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structural and Seismic Factors on the Constant-Strength Ductility Spectra Based on NGA-West2 Database

Abstract: The constant-strength ductility spectrum is a nonlinear response spectrum that is commonly used to establish the demand curve of the seismic response during performance-based seismic design. It is affected by many factors. In this paper, to evaluate the effect of the major influencing factors, including the structural parameters and seismic factors, the constant-strength ductility spectrum is calculated under different conditions based on 5535 ground motion records. Conclusions are drawn based on the mean cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Ji et al [11] studied the effect of the ductility demand coefficient on the constant-ductility strength demand spectrum, and they found that, with an increase or decrease in the ductility demand coefficient, the strength demand coefficient and the seismic resistance coefficient showed a specific variation law. In addition, the effects of k 2 , ζ, the hysteretic model, and pinching on the constant-strength ductility demand spectrum were also studied [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al [11] studied the effect of the ductility demand coefficient on the constant-ductility strength demand spectrum, and they found that, with an increase or decrease in the ductility demand coefficient, the strength demand coefficient and the seismic resistance coefficient showed a specific variation law. In addition, the effects of k 2 , ζ, the hysteretic model, and pinching on the constant-strength ductility demand spectrum were also studied [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%